'Clothing for the Soul Divine': Burials at the Tomb of St Ninian: Excavations at Whithorn Priory, 1957-67 - Lowe, Christopher E. (Archaeology report (Historic Scotland), 2015)
Whithorn, known as Scotland's Cradle of Christianity, is unique as a centre of worship, administration, and ultimately pilgrimage, dating back to the 5th century.The work carried out at Whithorn Priory by Roy Ritchie in the late 1950s and 1960s is the only modern excavation campaign to focus on the high status burials near the high altar of a major Scottish medieval church. Remains of earlier graves, as well as structures now recognised as parts of the extended medieval cathedral church, were uncovered. Among the uppermost level of graves are those that belong to a number of Whithorn's bishops, some of whom are tentatively named.This volume details the results of historical and scientific analysis of the remains of the bishops - who they were and where they came from, together with the circumstances of their deaths and burial. Many of these graves were richly furnished - including altar plate and the famous Whithorn crozier - and the full assemblage of artefacts from the excavation is published here for the first time. This publication also resolves, once and for all, the nature and date of the earliest graves that were identified at the base of the trench. The story of one of Scotland's most important 'lost excavations' can now be told.
Keywords: whithorn

Whithorn Priory. Burials at the tomb of St. Ninian - Faulkner, Neil (Current Archaeology, 2010)
Keywords: whithorn

Building Stone Sources for Whithorn Priory, Dundrennan Abbey And Other Historic Buildings In Galloway - Chadburn, Ray (Transactions of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 2007)
Keywords: whithorn

A monastery and its landscape : Whithorn and monastic estate management in Galloway (c. 1250-c. 1600) - Oram, Richard D. (Friends of the Whithorn Trust, 2005)
Keywords: whithorn

53 George Street, Whithorn: the late medieval priory gatehouse, together with a note on a series of possible ritual Marian marks - Lowe, Christopher E. (Transactions of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 2004)
Keywords: whithorn

Whithorn Priory in the Late Middle Ages - Dilworth, G. Mark (Whithorn Lectures, 1999)
Keywords: whithorn

Whithorn and St. Ninian: the excavation of a monastic town, 1984-91 - Hill, Peter H. (Sutton Publishing, 1998)
Keywords: whithorn

Whithorn: the missing years - Hill, Peter H. (Galloway. Land and Lordship, 1991)
Keywords: whithorn

Excavations at Whithorn Priory, 1972 and 1975 - Tabraham, Christopher J. (Transactions of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1979)
Keywords: whithorn

Excavating in Modern Way — Discoveries by Mine Detector (The Glasgow Herald, 1960)
Keywords: whithorn

Excavations at Whithorn, First Season, 1949 - Ralegh Radford, C.A. (Transactions of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1950)
Keywords: whithorn

The bishops and priors of Whithorn - Donaldson, Gordon (Transactions of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1949)
Keywords: whithorn

The Kintyre properties of the Whithorn priory and the bishopric of Galloway - McKerral, Andrew (Transactions of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1949)
Keywords: whithorn

The Priory Church at Whithorn - Kerr, Henry F. (Transactions of the Scottish Ecclesiological Society, 1934)
Keywords: whithorn

Whithorn Priory, Wigtownshire - Collingwood, William G.; Reid, R. C. (Ancient monuments and historic buildings, 1928)
Keywords: whithorn

The Priory of Whithern (Candida Casa) and its Lands and Churches in Mann - Talbot, Theophilus (W. Newby, 1900)
Keywords: whithorn; 🇮🇲 isle of man

Whithorn Priory - Dalrymple, Hew (Archæological and Historical Collections Relating to Ayrshire & Galloway, 1899)
Keywords: whithorn

The seal of the priory of Whithorn - Dalrymple, Hew (Archæological and Historical Collections Relating to Ayrshire & Galloway, 1894)
Keywords: whithorn